Investigation of non-tuberculous mycobacteria in a primary hospital from southeastern China - Pan, Xinling; Zhou, Yangxiao; Li, Zhaoxia; Zhang, Jun; Hong, Li; Shi, Yunzhen; Li, Guo-Gang (The Journal of Infection in Developing Countries, 2019)
Introduction: Non-tuberculous mycobacterium (NTM) can colonize the human body, leading to opportunistic infection. This study was conducted to analyze the NTM species composition in a primary hospital and investigate the potential features of the patients with different NTM species. Methodology: Mycobacterial strains were collected from the patients admitted at the hospital from January 2016 to May 2019. MPB64 assay was used to screen NTM strains and confirmed by Rv0577 amplification. The species were identified by hsp65 sequencing. The clinical records of patients with NTM were retrospectively reviewed. Results: Among the 122 identified NTM isolates, the most common strains were Mycobacterium avium complex (MAC, n = 102, 83.6%), Mycobacterium abscessus (n = 9, 7.4%) and Mycobacterium lentiflavum (n = 5, 4.1%). The predominant species among MAC were Mycobacterium chimaera (n = 57, 46.7%), followed by Mycobacterium intracellulare (n = 25, 20.5%) and Mycobacterium colombiense (n = 17, 13.9%). A significantly lower percentage of positive acid-fast assay was observed in Mycobacterium colombiense positive patients than in those with Mycobacterium intracellulare and Mycobacterium chimaera. Mycobacterium intracellulare was more frequently isolated in patients from the infectious department than in other MAC members. Conclusions: A predominant prevalence of Mycobacterium chimaera in Dongyang of Zhejiang Province was different from other regions in China, indicating that its prevalence has been likely underestimated. The heterogeneity in clinical features, caused by different MAC members, required an accurate species identification of the NTM isolated in the primary hospitals.